Network disruption detected in LY (Libya) - Voidly (2026)
CRITICAL severity disruption detected in Libya. Confidence: 70%. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: LY-2026-0001
Keywords: internet disruption; LY; disruption; critical